2014
DOI: 10.1038/nrg3687
|View full text |Cite
|
Sign up to set email alerts
|

X chromosome regulation: diverse patterns in development, tissues and disease

Abstract: Genes on the mammalian X chromosome are present in one copy in males and two copies in females. The complex mechanisms that regulate the X chromosome lead to evolutionary and physiological variability in gene expression between species, the sexes, individuals, developmental stages, tissues and cell types. In early development, delayed and incomplete X chromosome inactivation (XCI) in some species causes variability in gene expression. Additional diversity stems from escape from XCI and from mosaicism or XCI sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
248
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(254 citation statements)
references
References 127 publications
5
248
1
Order By: Relevance
“…As a coping strategy, many lineages have evolved various mechanisms of dosage compensation, which typically involve equalization of gene expression in males and females in conjunction with the evolution of adjusted expression ratios between sex-linked genes and their autosomal partners (Julien et al 2012;Graves 2016). In mammals, differences between males and females are reduced through female global X inactivation (Deng et al 2014), but birds lack any such chromosome-wide dosage compensation mechanism, and the resulting male-biased expression of Z-linked genes (Ellegren et al 2007;Itoh et al 2007;Mank and Ellegren 2009;Julien et al 2012) can therefore be assumed to prevent Z-linked and autosomal gene expression levels from being optimally adjusted in both sexes. That said, previous work has demonstrated that M:F expression ratios vary across Z-linked genes, such that the intrinsic male bias is counteracted for a subset of dosage-sensitive genes (Zimmer et al 2016), but it has not been clear how such gene-specific dosage compensation is achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a coping strategy, many lineages have evolved various mechanisms of dosage compensation, which typically involve equalization of gene expression in males and females in conjunction with the evolution of adjusted expression ratios between sex-linked genes and their autosomal partners (Julien et al 2012;Graves 2016). In mammals, differences between males and females are reduced through female global X inactivation (Deng et al 2014), but birds lack any such chromosome-wide dosage compensation mechanism, and the resulting male-biased expression of Z-linked genes (Ellegren et al 2007;Itoh et al 2007;Mank and Ellegren 2009;Julien et al 2012) can therefore be assumed to prevent Z-linked and autosomal gene expression levels from being optimally adjusted in both sexes. That said, previous work has demonstrated that M:F expression ratios vary across Z-linked genes, such that the intrinsic male bias is counteracted for a subset of dosage-sensitive genes (Zimmer et al 2016), but it has not been clear how such gene-specific dosage compensation is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In most mammals, females have two X Chromosomes, whereas males have one X and one Y Chromosome (Cortez et al 2014;Graves 2016), resulting in sexspecific gene dosage of X-linked and Y-linked genes. For the majority of genes, the effect on expression is mitigated through a dosage compensation mechanism in which one of the X Chromosomes is inactivated, although a fraction of genes are able to escape inactivation, thereby becoming more highly expressed in females (Deng et al 2014). Even so, the X Chromosome is generally associated with male-biased expression and is enriched for young, testis-expressed miRNAs (Guo et al 2009;Meunier et al 2013).…”
mentioning
confidence: 99%
“…Specifically, genomic imprinting induces the silencing of one of the alleles when it is transmitted by one of the parents, resulting in a parent-of-origindependent allelic transcription. [3][4][5] Owing to their monoallelic status, imprinted genes are easily affected by heterozygous deleterious mutations, CNVs, and alterations in expression dosage. For instance, some imprinted genes play a decisive role in growth control and developmental processes.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been well described in female mammalian cells, which transcriptionally inactivate the majority of genes on one randomly chosen X chromosome (Lyon 1986;Carrel and Willard 2005). X-chromosome inactivation occurs during the morula to blastocyst stage and is epigenetically maintained during subsequent mitotic cell divisions (Deng et al 2014). Autosomal genes can also undergo random monoallelic expression, with initial descriptions of its occurrence in immune genes (Mostoslavsky et al 2001) and the olfactory receptors (Chess et al 1994), providing cellular diversity within these systems.…”
Section: Introductionmentioning
confidence: 99%